The causes and impact of water shortage on the households of Ga-Kgapane Township in the Limpopo Province - Machethe, Elliot Masoto (University of Limpopo (Turfloop Campus), 2011)
Water shortage is a global problem. While other people in some parts of the world maybe enjoying enough supply of water others are faced with water shortage. South Africa is not an exception in this regard because some do not have access to water but rely on distance conveyance. Government is under constitutional obligation to supply this basic social and economic service. This study, therefore, aimed at investigating the causes of water shortage and the impact thereof on the household of Ga-Kgapane Township in Limpopo Province. This township falls under Greater Letaba Municipality in Modjadjiskloof. The data collected from four sections/localities of this Township showed that the area has a serious problem of water shortage. The lack of water according to the findings negatively affects the livelihoods and development of the people of Ga-Kgapane Township.
Thesis (M.Dev.) --University of Limpopo, 2011
Keywords: Water shortage; 553.70968; Water-supply, Rural -- South Africa